Moderators of pre-post changes in school-based mental health promotion: Psychological stress symptom decrease for adolescents with mental health problems, knowledge increase for all - Lehner, Laya; Gillé, Vera; Baldofski, Sabrina; Bauer, Stephanie; Becker, Katja; Diestelkamp, Silke; Kaess, Michael; Krämer, Jennifer; Lustig, Sophia; Moessner, Markus; Rummel-Kluge, Christine; Thomasius, Rainer; et al. (Frontiers in Psychiatry, 2022)
Background School-based mental health promotion aims to strengthen mental health and reduce stress. Results on the effectiveness of such programs are heterogeneous. This study realized a school-based mental health promotion program (StresSOS) for all students and aimed to identify moderators (mental health status, gender, grade level) of pre- to post-changes in stress symptoms and knowledge. Methods Participants were N = 510 adolescents (from 29 classes; 46.7% female) aged 12–18 years (M = 13.88, SD = 1.00; grade levels 7–10). They were without mental health problems (65.9%), at risk for mental health problems (21.6%), or with mental health problems (12.5%) and participated in a 90 min per week face-to-face training with 8 sessions in class at school. Demographic variables, mental health status, stress symptoms, and knowledge about stress and mental health were collected at baseline. Program acceptance, stress symptoms, and knowledge were collected post-intervention. Multilevel mixed effects models were conducted with the fixed effects time (within factor), mental health status, gender, and grade level (between factors). Random effects for students within classes were included. Results In the pre-post comparison, mental health status moderated the changes on psychological stress symptoms (p < 0.05). In adolescents with mental health problems the largest reduction in stress symptoms was observed between pre- and post-assessment. Gender and grade level were less relevant. For all adolescents knowledge gains were revealed (p < 0.001). Program acceptance was moderated by mental health status and grade level (p < 0.01). Mentally healthy adolescents and within the group of adolescents at-risk or with mental health problems, especially younger students (7th/8th grade), rated program acceptance higher. Conclusion Psychological stress symptoms decreased among adolescents with mental health problems and not among adolescents at risk for or without mental health problems. Mental health-related knowledge increased for all adolescents. The results add to knowledge on school-based mental health intervention research and practice. Its implications for different prevention strategies (universal, selective or a combination of both) are discussed.